The dark side of social media - Steffens, Bradley, 1955- (ReferencePoint Press, Inc., 2022)
"Social media can be used for good or for evil. In 2018, organizers of the March for Our Lives used social media to bring roughly 500,000 people to Washington, DC, to peacefully protest against gun violence--a powerful example of how social media can be used for good. But the Capitol insurrection on January 6, 2021 showed just as powerfully how social media can also be used for evil. Behavioral addiction is a mental health condition in which a person engages in a certain behavior, even if that behavior causes him or her harm"--